Properties of concrete with pumice powder and fly ash as cement replacement materials - Kabay, Nihat; Tufekci, M. Mansur; Kizilkanat, Ahmet B.; Oktay, Didem (ELSEVIER SCI LTD, 2015)
Turkey is rich in natural pozzolan and pumice is abundantly found in several regions of the country. In this study, pumice powder (PP) and fly ash (FA) were used as cement replacement materials and the effect of partial replacement of PP, FA and their blends by cement on physical, mechanical and durability properties of concrete was investigated. Test results showed both PP and FA addition resulted in lower mechanical strength at early ages, but comparable strength at later ages compared to the reference concrete. Replacement of cement with PP, FA and their blends resulted in concretes with decreased water absorption, sorptivity and void content and higher magnesium sulfate resistance compared to the reference concrete. Since pumice is abundantly found in Turkey, this material might be used as an additive in concrete applications or as a precaution against magnesium sulfate attack. (C) 2015 Published by Elsevier Ltd.
Keywords: Pumice powder; Fly ash; Strength development; Physical properties; Magnesium sulfate; SULFATE RESISTANCE; COMPRESSIVE STRENGTH; VOLCANIC ASH; PERFORMANCE; PLAIN; DURABILITY; Construction & Building Technology; Engineering; Materials Science